2019
DOI: 10.1093/ntr/ntz191
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Standards in the United States

Abstract: ImplicationsThis Special Issue on nicotine standards in the United States will address many of the questions raised in the Advance Notice of Proposed Rulemaking (ANPRM) through a series of policy commentaries and timely empirical studies across a variety of topic areas within the proposed comprehensive nicotine standards plan. The questions addressed in this issue include: (1) the threshold dose of nicotine (and other constituents) that would lead to minimally addictive cigarettes; (2) the effects of a nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…This paper builds on previous reviews of nicotine reduction research ( Berman & Glasser, 2019 ; Donny et al., 2014 ; Hatsukami, Perkins et al., 2010 ; Smith, Rupprecht et al., 2017 ; Stanton & Hatsukami, 2019 ), adding studies published through April 2021. We also extend these reviews by summarizing the available evidence on reduced uptake, as an additional category of behavioral response relative to public health impact.…”
Section: Introductionmentioning
confidence: 99%
“…This paper builds on previous reviews of nicotine reduction research ( Berman & Glasser, 2019 ; Donny et al., 2014 ; Hatsukami, Perkins et al., 2010 ; Smith, Rupprecht et al., 2017 ; Stanton & Hatsukami, 2019 ), adding studies published through April 2021. We also extend these reviews by summarizing the available evidence on reduced uptake, as an additional category of behavioral response relative to public health impact.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies shown that nicotine exposure poses potential risks to human health, since it is the main agent accountable for continued tobacco consumption, in addition to reacting during the burning of tobacco to form toxic compounds (Stepanov & Hatsukami, 2020;Gottlieb & Zeller, 2017;Benowitz & Henningfield, 2018;Wu, Ashley & Watson, 2003). Nowadays, a proposal to reduce and standardize nicotine contents within non-addictive levels in tobacco products, as well as for rulemaking, is already in place (Benowitz & Henningfield, 2018;Stanton & Hatsukami, 2019). Although there is a well-established method for nicotine analysis (CORESTA, 2005), development of chromatographic methods for determination of nicotine in tobacco products, such as tobacco leaves and STPs, has been often reported (Table 1).…”
Section: Nicotinementioning
confidence: 99%
“…Globally, there is already an eminent policy for tighter control of tobacco products, especially when it comes to smoke quitting interventions and public health issues related to nicotine and tobacco use and dependence (Gottlieb & Zeller, 2017;Benowitz & Henningfield, 2018;Stanton & Hatsukami, 2019). As a tobacco smoking prevention measure, some of the largest world producer countries of tobacco have banned the use of substances that provide aroma and flavor to tobacco-based smoking products, since they stimulate their consumption and, mainly, attract young smokers (ANVISA, 2012).…”
mentioning
confidence: 99%
“…3 Recently, a number of studies have evaluated the potential impact of a reduced-nicotine standard for cigarettes, including a recent special issue in Nicotine & Tobacco Research. 4 Overall, these studies have generally found abrupt transitions to reduced-nicotine cigarettes 5 and low nicotine levels (~0.4-mg nicotine per g of tobacco) would be beneficial in promoting smoking abstinence and reducing dependence and toxin exposure. 6 General recommendations from these studies suggest a successful nicotine product standard would incorporate noncombustible alternatives, promoting less-harmful products, and informing the public on the relative risks of nicotine products.…”
Section: Introductionmentioning
confidence: 99%